2020
DOI: 10.1002/1878-0261.12709
|View full text |Cite
|
Sign up to set email alerts
|

HPV‐related methylation‐based reclassification and risk stratification of cervical cancer

Abstract: Human papillomavirus (HPV) is a clear etiology of cervical cancer (CC). However, the associations between HPV infection and DNA methylation have not been thoroughly investigated. Additionally, it remains unknown whether HPV‐related methylation signatures can identify subtypes of CC and stratify the prognosis of CC patients. DNA methylation profiles were obtained from The Cancer Genome Atlas to identify HPV‐related methylation sites. Unsupervised clustering analysis of HPV‐related methylation sites was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…Hippo hijacks EGFR and HPV E6 oncoprotein to promote CC, 58 and its downstream YAP and TAZ proteins play a role in cervical tumor‐infiltrated cell activation 59 . Previously study finds that mutation, amplification, and deletions of Hippo in hypermethylated CC subgroup 60 . We provided additional evidences that methylated genes in Hippo pathway occurred in CC, even at CINs stages.…”
Section: Discussionsupporting
confidence: 56%
“…Hippo hijacks EGFR and HPV E6 oncoprotein to promote CC, 58 and its downstream YAP and TAZ proteins play a role in cervical tumor‐infiltrated cell activation 59 . Previously study finds that mutation, amplification, and deletions of Hippo in hypermethylated CC subgroup 60 . We provided additional evidences that methylated genes in Hippo pathway occurred in CC, even at CINs stages.…”
Section: Discussionsupporting
confidence: 56%
“…HPV oncoproteins were shown to modulate DNMT1 levels [ 19 , 20 , 34 ] and some studies have been developed to identify HPV-associated alterations of DNA methylation in cervical cancer [ 35 , 36 , 37 ]. This led to the design of gene panels whose methylation levels can discriminate tumors from non-tumor tissues as well as predict preneoplastic lesions more likely to progress, with high accuracy [ 35 , 38 , 39 , 40 ]. However, in head and neck cancer, the association between HPV infection and DNA methylation aberration has been less explored, both genome-wide and in target genes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been estimated that microbiota may be associated with more than 20% of malignancies [ 35 ], but the role of only few microorganisms as carcinogens is widely known and well established. Among the few, one has to include Helicobacter pylori (gastric cancer), Schistosoma haematobium (urinary BC), and human papilloma viruses (cervical and penile cancers) [ 36 , 37 , 38 , 39 , 40 , 41 ]. Studies of the gut, pancreatic, and breast microbiome revealed a multifactorial association between microbiota and cancer [ 35 , 42 , 43 ] and, although the mechanisms of the microbiome interaction with human cells are extremely complex, they involve at least one of these three phenomena: direct influence on host cells’ proliferation and death, modulation of innate immune system, and interaction with host biochemistry [ 44 ].…”
Section: Microbiota and Tumorigenesismentioning
confidence: 99%